2003
DOI: 10.1016/s0960-9822(03)00210-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional Conservation of the Telomerase Protein Est1p in Humans

Abstract: Eukaryotic telomerase contains a telomerase reverse transcriptase (TERT) and an RNA template component that are essential for telomerase catalytic activity and several other telomerase-associated factors of which only a few appear to be integral enzyme components [1-3]. The first essential telomerase protein identified was S. cerevisiae Est1p, whose deletion leads to ever-shorter telomeres despite the persistence of telomerase activity [4-6]. Extensive genetic and biochemical data show that Est1p, via its inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
155
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(162 citation statements)
references
References 37 publications
6
155
0
1
Order By: Relevance
“…Est1 is a fundamental telomere DNA maintenance factor that is conserved from yeast to human (10,21). Genetic experiments in yeast have suggested an Est1-role in both recruiting and activating telomerase (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Est1 is a fundamental telomere DNA maintenance factor that is conserved from yeast to human (10,21). Genetic experiments in yeast have suggested an Est1-role in both recruiting and activating telomerase (3).…”
Section: Discussionmentioning
confidence: 99%
“…Prior biochemical studies demonstrate that yeast and human Est1 bind single-stranded G-rich DNA and apparently recognize RNA nonspecifically in vitro (9)(10)(11). In contrast to the in vitro work, in vivo studies indicate that yeast Est1 targets a bulged-stem loop in the TLC1 telomerase RNA (12, 13).…”
mentioning
confidence: 99%
“…In the absence of detectable changes in the level of telomerase activity, the eventual stabilization of telomere length points to alterations in telomere-associated proteins leading to better utilization of the telomerase present in the cells, possibly through improved recruitment of the enzyme to the telomere. Human orthologs to yeast Est1 and Cdc13, which mediate access of telomerase to telomeres (45), have recently been identified (46,47) and may play a similar role in telomere stabilization in human cells. The additional genetic changes in postcrisis T2a cells (34) provide a starting point for investigating the molecular basis of telomere length regulation in human hematopoietic cells.…”
Section: Discussionmentioning
confidence: 99%
“…22 Similarly to ScEst1p, human EST1A/SMG6 interacts with active telomerase in human cells. 19,20 While EST1 deletion in yeast leads to a progressive shortening of the telomeres and after 60-80 population doublings to cellular senescence, shRNA-mediated depletion of human EST1A/SMG6 causes a rapid cell cycle arrest after a few population doublings (our unpublished data), rendering the detection of a putative telomere shortening phenotype impossible. Nevertheless, overexpression of EST1A/SMG6 in human cell lines leads to the accumulation of chromosomal end-to-end fusions suggesting a role for EST1A/SMG6 in maintaining the normal structure of human chromosome ends.…”
mentioning
confidence: 93%
“…We and others have previously demonstrated that human EST1A, which is identical to the NMD factor SMG6, shares sequence similarity with Est1p from Saccharoymces cerevisiae. [19][20][21] ScEst1p is an essential core component of the telomerase enzyme, which adds telomeric repeats to the termini of chromosomes (the telomeres), to counteract telomere loss due to incomplete end replication. 22 Similarly to ScEst1p, human EST1A/SMG6 interacts with active telomerase in human cells.…”
mentioning
confidence: 99%